Analisis Micromanagement Pemimpin terhadap Kinerja Pegawai: Studi Kasus Keryawan Alfamart Magelang Utara - Chelsea Aulia Pratiwi; Desfin Setyaningrum; Muhammad Yosa Al Islam; Khoirotul Anisa’; Nova Herliyana Putri (Universitas Fajar, 2026)
This study aims to examine the impact of micromanagement leadership styles on employee productivity at Alfamart in North Magelang. The focus of this research problem is related to overly strict supervision from superiors, limited freedom in employee decision-making, and their impact on productivity and work motivation. The method used in this research is a qualitative case study approach. Data were collected through in-depth interviews with several purposively selected Alfamart employees in North Magelang. The findings of this study reveal that micromanagement practices have varying effects on employee performance. Detailed supervision can improve discipline and facilitate faster task completion, but it also creates work pressure, lowers self-confidence, and inhibits employee creativity and initiative. In addition, excessive control from superiors affects the effectiveness of communication between leaders and employees. The uniqueness of this study lies in analyzing micromanagement practices in the modern retail sector, specifically within the work context at Alfamart. The implications of this research demonstrate the importance of implementing a more balanced leadership style to ensure employee comfort at work, well-being, and the development of potential. Keywords—Leadership; Employee Performance; Micromanagement; Work Motivation; Productivity